1997
DOI: 10.1074/jbc.272.33.20545
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-induced Hypertrophic Growth of Cardiocytes and Processing of Brain-type Natriuretic Peptide Are Controlled by Proprotein-processing Endoprotease Furin

Abstract: When hypertrophic growth is induced in neonatal rat cardiocytes by stretching, the cardiocytes express high levels of brain-type natriuretic peptide (BNP) and the proprotein-processing enzyme furin. A BNP precursor, ␥BNP, possesses a furin-cleavable Arg-X-X-Arg motif, which is cleaved when ␥BNP is processed to form BNP-45. The Arg-X-X-Arg motif is found in many precursors of growth factors and growth-related proteins. To determine if furin converts ␥BNP to BNP-45 as well as other unidentified growth-promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
1
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 74 publications
0
80
1
5
Order By: Relevance
“…Moreover, this event occurs during or very close to exocytosis of the secretory granules, since the peptide stored in the heart consists almost solely of pro-sCP-sized material, while the secreted peptide is due to sCP-sized material. Finally, the furin motif Arg-X-X-Arg (Sawada et al 1997) is not present in pro-sCP (Tervonen et al 1998), precluding BNP-type processing. On the other hand, it is interesting to note that the gene, cDNA and amino acid sequence of sCP (Tervonen et al 1998, Majalahti-Palviainen et al 2000 show a mixture of features typical of all three previously known mammalian natriuretic peptide subgroups, ANP, BNP and CNP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this event occurs during or very close to exocytosis of the secretory granules, since the peptide stored in the heart consists almost solely of pro-sCP-sized material, while the secreted peptide is due to sCP-sized material. Finally, the furin motif Arg-X-X-Arg (Sawada et al 1997) is not present in pro-sCP (Tervonen et al 1998), precluding BNP-type processing. On the other hand, it is interesting to note that the gene, cDNA and amino acid sequence of sCP (Tervonen et al 1998, Majalahti-Palviainen et al 2000 show a mixture of features typical of all three previously known mammalian natriuretic peptide subgroups, ANP, BNP and CNP.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNPspecific MAbs (with the recognized region as s subscript) 5B6 [1][2][3][4][5][6][7][8][9][10][11][12] , 29D12 [5][6][7][8][9][10][11][12] , 13G12 [13][14][15][16][17][18][19][20] , 21E3 [13][14][15][16][17][18][19][20][21][22][23][24] , 1D4 [13][14][15][16][17][18][19][20][21][22][23][24] , 16F3 [13][14][15]…”
Section: Recombinant Proteins and Monoclonal Antibodiesunclassified
“…Recently, we have demonstrated that NT-proBNP in human blood is also glycosylated and that glycosylation negatively influences the recognition of NT-proBNP by antibodies specific to the central part of the molecule (5 ). For several years, 2 proprotein convertases, furin and corin, have been discussed in the literature as possible candidates responsible for proBNP processing (10,11 ), but the question of which of these 2 enzymes (and possibly other convertases) is responsible for proBNP processing in cardiomyocytes remains unanswered.…”
Section: Probnp Processing Is Suppressed By O-glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The former exhibits the biological activity, whereas no defined biological function has been found to be associated with the latter. The processing site in proBNP occurs immediately downstream from the Arg 73 -X-X-Arg 76 sequence, at a cleavage site similar to that recognized by the ubiquitous endoprotease furin (7,8 ). However, other endoproteases, such as corin (9,10 ), or prohormone convertases (11 ) may be involved in the posttranslational maturation of proBNP .…”
mentioning
confidence: 99%